Identification of Pyruvate Dehydrogenase E1 as a Potential Target against Magnaporthe oryzae through Experimental and Theoretical Investigation - Yuejuan Li (International Journal of Molecular Sciences, 2021)
Magnaporthe oryzae (M. oryzae) is a typical cause of rice blast in agricultural production. Isobavachalcone (IBC), an active ingredient of Psoralea corylifolia L. extract, is an effective fungicide against rice blast. To determine the mechanism of IBC against M. oryzae, the effect of IBC on the metabolic pathway of M. oryzae was explored by transcriptome profiling. In M. oryzae, the expression of pyruvate dehydrogenase E1 (PDHE1), part of the tricarboxylic acid (TCA cycle), was significantly decreased in response to treatment with IBC, which was verified by qPCR and testing of enzyme activity. To further elucidate the interactions between IBC and PDHE1, the 3D structure model of the PDHE1 from M. oryzae was established based on homology modeling. The model was utilized to analyze the molecular interactions through molecular docking and molecular dynamics simulation, revealing that IBC has π-π stacking interactions with residue TYR139 and undergoes hydrogen bonding with residue ASP217 of PDHE1. Additionally, the nonpolar residues PHE111, MET174, ILE 187, VAL188, and MET250 form strong hydrophobic interactions with IBC. The above results reveal that PDHE1 is a potential target for antifungal agents, which will be of great significance for guiding the design of new fungicides. This research clarified the mechanism of IBC against M. oryzae at the molecular level, which will underpin further studies of the inhibitory mechanism of flavonoids and the discovery of new targets. It also provides theoretical guidance for the field application of IBC.